Interactive 3D tour around FSKTM / Khairul Efeeza Ismail - Khairul Efeeza , Ismail (2004)
Now days, 3D’s designs has become popular among the top designers. Even now revolutionaries of the cell phone screen interface had become in 3D’s. 3D’s also had been used worldwide as a virtual mapping of an place as part of their information systems. According to this thesis title- Interactive 3D tour around FSKTM is an interactive 3D virtual FSKTM system. This system enables the users to view FSKTM virtually FSKTM environments without have to come physically to FSKTM. Interactive environments will power this system as part of the interactive way of making people attractively using system. Target of the is to proving FSKTM with 3D’s information technologies as 3D’s design are something new here and with this system will ease FSKTM visitors or new students to find a certain place in FSKTM. The target users are students it self, lecture as well tourist. Using 3DgameStudio as well as 3DstudioMax as the software development tools will develop this system. The system is developed on Microsoft Window XP operating system due to its stability. With this system, hopefully 3D map will be using worldwide as part of their informational. Furthermore, hope the faculty will use this project as it informational of the faculty as the first ever design of visual FSKTM faculty.